Cryoablation synergizes with anti-PD-1 immunotherapy induces an effective abscopal effect in murine model of cervical cancer - Xiaoming Yang; Xiaoyan Gao; Chen Xu; Ting Ni; Yaru Sheng; Jing Wang; Xiao Sun; Jiangjing Yuan; Lin Zhang; Yudong Wang (Translational Oncology)
Background: Immune checkpoint inhibitors (ICIs), especially anti-PD-1/PD-L1 antibodies, have emerged as promising therapeutic options for cervical cancer. However, the efficacy of anti-PD-1 antibody monotherapy is limited. Cryoablation could elicit an anti-tumor immune response, thereby presenting itself as a potential approach to augment the response of ICIs. The aim of our study was to investigate the systemic immunological effects of cryoablation and the potential synergistic anti-tumor effects of cryoablation and anti-PD-1 antibody in cervical cancer. Methods: We established U14 murine bilateral subcutaneous cervical cancer model, wherein the primary tumors were treated with cryoablation. Flow cytometry, immunohistochemistry and RNA-seq were used to analyze the immune cell infiltration and immune-associated pathways in the secondary tumor. Results: Our study revealed that cryoablation reprogrammed the immune landscape, leading to an enhanced infiltration of CD8+ T cell in distant tumors. Cryoablation created a conducive environment for increasing the efficacy of anti-PD-1 immunotherapy. Cryoablation in combination with anti-PD-1 antibody inhibited distant tumors growth and improved mouse survival. Mechanistically, this combination therapy could augment the infiltration of CD8+ T cells, CD4+ T cells, dendritic cells and M1-like tumor-associated macrophages, enhance multiple aspects of antitumor immune response, and reduce immunosuppressive cells such as M2-like tumor-associated macrophages and myeloid-derived suppressor cells in distant tumors. Conclusions: Combination therapy with cryoablation and anti-PD-1 antibody induces an effective abscopal effect in murine model of cervical cancer and may be a novel therapeutic approach for patients with advanced/recurrent cervical cancer.